Cover Picture: A Mass Spectrometric Approach for Probing the Stability of Bioorganic Radicals (Angew. Chem. Int. Ed. 7/2014). Issue 7 (20th January 2014) - Tan, Lei; Hu, Hanfeng; Francisco, Joseph S.; Xia, Yu
<x xml:space="preserve">Abstract</x> Radical stability can be assessed by a new mass spectrometric approach proposed by L. Tan and co‐workers in their Communication on page 1887 ff. The stability of carbon‐centered bioorganic radicals is evaluated by a method based on the gas‐phase dissociation of sulfinyl radical ions. The degree of CH2SO loss is found to be correlated with the stability of the as‐formed radical species, which can be molecularly tuned by the electronic effect of the neighboring groups.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>